ANP applied to the evaluation of performance indicators of reverse logistics in footwear industry - Silveira Guimaraes, Jose Leonardo da; Pamplona Salomon, Valerio Antonio [UNESP]; Gomes, LFAM; Colcher, R.; Wolcott, P.; HerreraViedma, E.; Shi, Y. (Elsevier B.V., 2015)
The reverse logistics (RL) seeks to facilitate the return of consumer goods, or its constituent materials, in the production cycle. The main motivators of RL are economic factors, customer service, legal, corporate citizenship and corporate image. The evaluation of RL practices involves therefore multiple interrelated aspects: environmental legislation, technology, costs, external relations etc. This article aims to present an assessment of the priorities of the indicators of reverse logistics in a small footwear industry in the Brazilian State of Ceara. The model of RL evaluation applies the Analytic Network Process, because it allows assessing dependency relationships or existing influence. (C) 2015 Published by Elsevier B.V.
Keywords: Multiple criteria decision making; Reverse logistics; Analytic network process; Performance indicators; Footwear industry